Preparation method of low-overpotential anode and application of low-overpotential anode in electrocatalytic water splitting oxygen desorption
By displacing the deposit of uranium and/or thorium and iron elements on the foam nickel support, it is used as a low overpotential anode for electrocatalytic water cracking to resolve oxygen, solving the problems of high cost and low efficiency of precious metals, and achieving high efficiency and stability electrocatalytic properties.
Patent Information
- Application Number
- CN202411256954.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-09
AI Technical Summary
Traditional OER electrocatalysts rely on precious metals, have high costs and scarce resources, which limit their large-scale application. The oxygen evolution reaction efficiency during the electrolysis process is low, affecting the overall water decomposition performance.
Using nickel foamed with molybdenum metal as a support, uranium and/or thorium and iron elements are deposited through elemental replacement reactions to form corresponding oxides, and their interactions are enhanced by calcination, and used as low overpotential anode for electrocatalytic water cracking analysis oxygen.
The overpotential is significantly reduced, the stability and catalytic efficiency of the catalyst are improved, the hydrogen evolution activation energy is reduced, and excellent electrocatalytic performance in alkaline water and alkaline seawater is achieved.
Smart Images

Figure CN119121273A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrochemistry, and in particular to a method for preparing a low overpotential anode and application of the anode in electrocatalytic water splitting and oxygen resolution. Background Art
[0002] With the growing global demand for renewable energy and increasingly severe environmental problems, the development of efficient and sustainable energy conversion technologies has become particularly urgent. Hydrogen production by water electrolysis, as a clean and efficient way to produce hydrogen, is gradually becoming a research hotspot. However, the oxygen evolution reaction (OER) in the water electrolysis process often becomes a key kinetically limited step due to its complex four-electron transfer process, and its efficiency directly affects the overall water decomposition performance. Traditionally, OER electrocatalysts rely on precious metals such as iridium and ruthenium, but these materials are not only expensive, but also scarce in resources, which limits their large-scale application. Therefore, the development of efficient, stable and low-cost non-precious metal electrocatalysts has become an urgent need for current research.
[0003] In recent years, polymetallic oxides have shown great potential in the field of OER catalysis due to their adjustable electronic structure, abundant catalytic active sites and good stability. Researchers have continuously improved the catalytic performance of polymetallic oxides by adjusting metal composition and optimizing material structure. However, how to further reduce the cost of catalysts while ensuring catalytic activity is still an important research direction. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a method for preparing a low overpotential anode and its application in electrocatalytic water splitting and oxygen analysis. The anode prepared by the present invention uses nickel foam loaded with molybdenum metal as a carrier, and then replaces and deposits uranium and / or thorium and iron elements on the carrier through a substitution reaction between elements, and finally strengthens the interaction between the deposited elements and the carrier through calcination to form corresponding oxides of the metal elements therein. It is used as an anode for electrocatalytic cracking of alkaline water or alkaline seawater for oxygen analysis, with reduced overpotential and strong stability.
[0005] The specific technical scheme of the present invention is:
[0006] First, the present invention provides a method for preparing a low overpotential anode, comprising the following steps:
[0007] 1) The nickel foam is pre-treated by pickling, and then loaded with molybdenum metal to obtain nickel-molybdenum foam.
[0008] 2) Immerse the foamed nickel molybdenum in a soaking solution containing uranium and / or thorium metal salts and iron salts to carry out a replacement reaction, and then take it out and dry it.
[0009] 3) The product obtained in step 2) is calcined with oxygen to obtain a low overpotential anode.
[0010] The anode prepared by the above method of the present invention uses foamed nickel molybdenum as a carrier, and through the replacement reaction between elements, uranium and / or thorium and iron elements are replaced and deposited on the carrier, and finally calcined to strengthen the interaction between the deposited elements and the carrier and make the metal elements therein form corresponding oxides.
[0011] The present invention finds that the above-mentioned material is applied as an anode to electrocatalytic cracking of alkaline water or alkaline seawater for oxygen evolution, with reduced overpotential and strong stability. The reason for this is that the interaction between the above-mentioned specific four metal elements can promote the movement of d-band electrons to low energy levels, so that the overlap between the metal 3d orbital and the 2p orbital of oxygen increases, and promotes the orbital hybridization between the two. The enhancement of this orbital hybridization effect not only strengthens the transfer ability of electrons between metal and oxygen, but also significantly weakens the originally strong metal-oxygen bond, so that the covalent connection between the lattice oxygen and the metal in the anode material is weakened, becoming more active, thereby improving the catalytic efficiency of the anode in the electrocatalytic reaction. In addition, through the nuclear radiation of a small amount of uranium and / or thorium, water molecules can be pre-activated and are in an easily dissociated state, further reducing the activation energy required for hydrogen evolution.
[0012] In addition, the present invention also found that the ratio of uranium and / or thorium to iron and the calcination conditions have a crucial influence on the performance of the anode. Specifically:
[0013] The present invention preferably has a molar ratio of uranium and / or thorium to iron of 1:10-15. Different ratios of uranium and / or thorium to iron have a great influence on the performance of electrode materials. Taking uranium as an example, the presence of uranium pre-activates water molecules and promotes their dissociation. The addition of iron enhances the interaction between metals, thereby significantly improving the electrocatalytic performance. Excessive addition of iron will mask the active sites of the reaction, affect the adsorption of water molecules, and thus suppress the performance.
[0014] The preferred calcination temperature of the present invention is 100-200°C and the time is 0.5-1.5h. Different calcination temperatures significantly affect the electrocatalytic performance of the electrode material. When the calcination temperature is low, the metal on the material is not completely oxidized and a strong metal oxide cannot be formed; the present invention finds that when the calcination temperature exceeds 200°C, the excessively high temperature causes the carrier to be damaged and the basic structure cannot be maintained, resulting in reduced performance.
[0015] Furthermore, in step 1), the method of loading molybdenum element on nickel foam includes immersion replacement method, electroplating method or high temperature reduction method, and immersion replacement method is more preferred. The mass ratio of nickel to molybdenum is 3-8:1.
[0016] Furthermore, in step 1), the thickness of the nickel foam is 1-2 mm, the pore size is 80-150 ppi, and the area range is 0.0001-10 m 2 More preferably, the area of the nickel foam is in the range of 0.02-0.1 m 2 ;
[0017] Furthermore, in step 1), the pickling specifically comprises: placing the nickel foam in 0.5-1.5 mol·L -1 The sample was ultrasonically cleaned in a dilute hydrochloric acid solution for 20-40 minutes, taken out and immersed in anhydrous ethanol for ultrasonic cleaning for 20-40 minutes, and dried.
[0018] Furthermore, in step 2), the uranium and / or thorium metal salt is uranyl nitrate hexahydrate or thorium nitrate hydrate; and the iron salt is one or more of ferric sulfate, ferric nitrate and ferric chloride.
[0019] Furthermore, in step 2), the iron content in the soaking solution is 0.05-0.2 mol·L -1 The ratio of the area of the nickel foam to the amount of the soaking liquid is 0.8-5cm -2 / ml.
[0020] Furthermore, in step 2), the replacement reaction time is 10-60 min, more preferably 30-50 min.
[0021] Secondly, the present invention provides the use of the low overpotential anode obtained by the above preparation method in the electrocatalytic cracking of alkaline water or oxygen evolution of alkaline seawater.
[0022] The anode prepared by the present invention exhibits excellent performance in the electrocatalytic water splitting oxygen release reaction. The presence of multi-metal greatly promotes the dynamic reconstruction ability of the catalyst itself and significantly accelerates the high-valent nickel ion (Ni 3+ / Ni 4+ ) formation process. In alkaline water electrolyte, it reaches 100mA·cm -2 The current density required is 204mV, which significantly reduces the energy consumption. In addition, it also has excellent catalytic performance in complex alkaline seawater electrolyte. -2 The minimum overpotential required for the current density is 234mV. It has good stability in alkaline water and alkaline seawater. In a week of electrocatalytic oxygen evolution test, its current density only decreased by about 10%.
[0023] Furthermore, the alkaline medium in the alkaline water or alkaline seawater electrolyte system is sodium hydroxide or potassium hydroxide.
[0024] Furthermore, the concentration of the sodium hydroxide or potassium hydroxide is 10-50wt%.
[0025] Compared with the prior art, the beneficial effects of the present invention are:
[0026] (1) The anode prepared by the present invention uses nickel foam as a carrier, firstly loads molybdenum on it, and then replaces uranium and / or thorium and iron on the carrier through substitution reaction between elements, and finally strengthens the interaction between the deposited elements and the carrier through calcination to form corresponding oxides of the metal elements therein. It is used as an anode for electrocatalytic cracking of alkaline water or alkaline seawater oxygen evolution, and has a reduced overpotential and strong stability.
[0027] (2) The present invention further improves the electrocatalytic performance of the anode by optimizing the ratio of uranium and / or thorium and iron and the calcination conditions.
[0028] (3) The present invention provides an innovative method for the utilization and treatment of nuclear waste. Recycling spent nuclear fuel after nuclear reactions into electrocatalytic anodes can maximize the potential energy value contained in these wastes and realize the recycling of resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 SEM image of the FeUNiMo quaternary electrode material prepared in Example 1 of the present invention; Figure 2 The activity test results of the electrocatalytic oxygen evolution electrodes in Test Example 1 and Test Example 2; Figure 3 The electrocatalytic oxygen evolution electrode in Experimental Example 1 and Experimental Example 2 is 100 mA·cm -2 The required overpotential; Figure 4 The activity test results of the electrocatalytic oxygen evolution electrode in Experimental Example 3; Figure 5 The activity test results of the electrocatalytic oxygen evolution electrode in Test Example 4; Figure 6 The activity test results of the electrocatalytic oxygen evolution electrode in Test Example 5; Figure 7 The activity test results of the electrocatalytic oxygen evolution electrode in Test Example 6; Figure 8 The stability test results of the electrocatalytic oxygen evolution electrode in Experimental Example 7; Fig. 9 This is the stability test result of the electrocatalytic oxygen evolution electrode in Experimental Example 8. DETAILED DESCRIPTION
[0037] The present invention will be further described below in conjunction with the embodiments.
[0038] Example 1
[0039] The preparation process of FeUNiMo (FUNM) quaternary electrode material is as follows:
[0040] Carrier pretreatment: Place 1 mol·L nickel foam with a pore size of 100 ppi, a thickness of 1.5 mm, and a size of 1*2 cm in a -1 The sample was placed in a dilute hydrochloric acid solution, ultrasonically cleaned for 30 minutes, then taken out, placed in anhydrous ethanol and ultrasonically cleaned for 30 minutes, and then dried.
[0041] Molybdenum metal loading: put the pretreated nickel foam into 50ml, with a concentration of 0.5mol·L -1 Electroplating was carried out in a sodium molybdate solution with an applied current of 0.5 mA cm -1 , the electroplating time is 5 minutes. After electroplating, nickel foam loaded with molybdenum metal (i.e., nickel foam molybdenum) is obtained, and the mass ratio of nickel to molybdenum is 9:1.
[0042] Synthesis of FeUNiMo quaternary electrode material: Put nickel molybdenum foam into 10 ml of 0.0502 g uranyl nitrate hexahydrate (0.01 mol·L -1 ) and 0.404 g ferric nitrate nonahydrate (0.10 mol·L -1 ) in the soaking solution, stand for 40 minutes, take it out and put it into the oven, dry it at 60°C, put it into the muffle furnace, heat it to 200°C at a heating rate of 5°C / min, and keep it warm for 1 hour. After cooling to room temperature, take it out to obtain the FeUNiMo catalytic electrode. Figure 1 From its SEM image, we can see that its surface is rough and a layer of replaced metal oxide is deposited, which is conducive to the electrolysis reaction.
[0043] Example 2
[0044] The preparation method is the same as that in Example 1, except that the calcination is not performed in a muffle furnace.
[0045] Example 3
[0046] The preparation method is the same as that of Example 1, with the specific difference being that the calcination and insulation temperature in the muffle furnace is 100°C.
[0047] Example 4
[0048] The preparation method is the same as that in Example 1, the specific difference is that the calcination and insulation temperature in the muffle furnace is 300°C.
[0049] Example 5
[0050] The preparation method is the same as that of Example 1, except that the concentration of ferric nitrate nonahydrate in the soaking solution is 0.05 mol·L -1 .
[0051] Example 6
[0052] The preparation method is the same as that of Example 1, except that the concentration of ferric nitrate nonahydrate in the soaking solution is 0.15 mol·L -1 .
[0053] Example 7
[0054] The preparation method is the same as that of Example 1, except that the concentration of ferric nitrate nonahydrate in the soaking solution is 0.20 mol·L -1 .
[0055] Example 8
[0056] The preparation method is the same as that in Example 1, with the specific difference being that the soaking time is 10 minutes.
[0057] Example 9
[0058] The preparation method is the same as that in Example 1, with the specific difference being that the soaking time is 20 minutes.
[0059] Example 10
[0060] The preparation method is the same as that in Example 1, with the specific difference being that the soaking time is 30 minutes.
[0061] Embodiment 11
[0062] The preparation method is the same as that in Example 1, with the specific difference being that the soaking time is 50 minutes.
[0063] Example 12
[0064] The preparation method is the same as that in Example 1, with the specific difference being that the soaking time is 60 minutes.
[0065] Example 13
[0066] The preparation method is the same as that of Example 1, except that 0.0502 g of uranyl nitrate hexahydrate in the soaking solution is replaced with 0.0480 g of thorium nitrate hydrate (0.01 mol·L -1 ), and the obtained product was recorded as FTNM.
[0067] Embodiment 14
[0068] The preparation method is the same as that in Example 1, except that the pretreated nickel foam is immersed in 25 ml of 0.05 mol·L -1The product was denoted as FUNM-2, and the mass ratio of nickel to molybdenum was 9:1.
[0069] Embodiment 15
[0070] The preparation method is the same as that in Example 1, the specific difference is that no electroplating treatment is performed, the immersion liquid is ultrapure water without any metal salt, and the obtained product is recorded as N.
[0071] Example 16
[0072] The preparation method is the same as that of Example 1, except that the soaking solution contains only 0.0502 g of uranyl nitrate hexahydrate (0.01 mol·L -1 ), and the obtained product was recorded as UNM.
[0073] Embodiment 17
[0074] The preparation method is the same as that of Example 1, except that the soaking solution contains only 0.404 g of ferric nitrate nonahydrate (0.10 mol·L -1 ), and the obtained product was recorded as FNM.
[0075] Embodiment 18
[0076] The preparation method is the same as that of Example 1, with the specific difference being that the soaking liquid is ultrapure water without any metal salt, and the obtained product is recorded as NM.
[0077] Performance Testing
[0078] Test Example 1
[0079] The electrode materials prepared in Example 1 and Examples 16-18 were subjected to linear sweep voltammetry test in 5wt% KOH solution. The specific test used a saturated Ag / AgCl electrode as the reference electrode, a graphite electrode as the counter electrode, a sweep rate of 10mV / s, and a 5wt% KOH electrolyte. The electrode potentials were all iR-corrected to eliminate the effects of solution resistance, etc., and converted into electrode potentials relative to the reversible electrode (RHE), and the calculation formula is: Overpotential (V) = Electrode potential + pH*0.0591 + 0.1976-1.23. The results are shown in Figure 2 The solid line in .
[0080] Figure 3 100 mA cm for four electrode materials -2 The overpotential at a current density of Figure 3It can be seen that the quaternary electrode material has the best electrocatalytic water splitting performance. The overpotential is only 204mV, and the catalytic performance of the ternary material is also better than that of the binary support. It shows that the addition of Fe and U promotes the catalytic electrode, and the coexistence of the two can further synergistically improve the catalytic performance. Due to the direct interaction between multiple metals and the interaction with the connecting oxygen, the center of the metal d band moves down, the orbital hybridization between the metal 3d and O 2p orbitals is enhanced, and the covalent interaction between MO is enhanced. This enhancement effect can enhance the dynamic response of the catalyst's self-reconstruction during the catalytic process, which is conducive to the rapid activation of the OER performance that follows the lattice oxygen mechanism.
[0081] Test Example 2
[0082] The electrode materials prepared in Example 1 and Examples 16-18 were subjected to linear sweep voltammetry test in 5wt% KOH seawater. The specific test used a saturated Ag / AgCl electrode as the reference electrode, a graphite electrode as the counter electrode, a sweep rate of 10mV / s, and an electrolyte of 5wt% KOH seawater. The electrode potentials were all iR corrected to eliminate the effects of solution resistance, etc., and converted into electrode potentials relative to the reversible electrode (RHE), and the calculation formula is: Overpotential (V) = Electrode potential + pH*0.0591 + 0.1976-1.23. The results are shown in Figure 2 The dotted line in .
[0083] Figure 3 100 mA cm for four materials -2 As can be seen from the figure, in more complex seawater, the material needs to reach 100mA·cm -2 The potential required for the current density is higher than that of pure alkali water, but the overpotential of the quaternary material is still the smallest, only 234mV. The performance of the ternary material is also better than that of the binary carrier material. This shows that the prepared material still has strong adaptability and wide application potential in more complex seawater, and plays an important role in the development and protection of the ocean.
[0084] Test Example 3
[0085] The electrode materials prepared in Example 1 and Examples 16-18 were subjected to linear sweep voltammetry in a 5wt% KOH solution to explore the effects of different methods of loading molybdenum on material properties. The specific test method is the same as that of Experimental Example 1. The results are shown in Figure 4 .
[0086] Loading molybdenum metal onto the surface of nickel foam using different methods has no significant effect on the performance of the material, and its performance is significantly improved compared to simple nickel foam.
[0087] Test Example 4
[0088] The electrode materials prepared in Examples 1-4 were subjected to linear sweep voltammetry in a 5 wt% KOH solution to explore the effect of calcination temperature on material properties. The specific test method was the same as that in Experiment 1. The results are shown in Figure 5 .
[0089] Different calcination temperatures significantly affect the catalytic performance of electrode materials. When the calcination temperature is low, the metal on the material is not completely oxidized and a solid metal oxide cannot be formed; when the calcination temperature exceeds 200°C, the carrier is damaged by the excessively high temperature and cannot maintain the basic structure, resulting in reduced performance.
[0090] Test Example 5
[0091] The electrode materials prepared in Example 1, Examples 5-7 and Comparative Example 1 were subjected to linear sweep voltammetry tests in a 5wt% KOH solution to explore the effects of different metal salt concentration ratios on material performance. The specific test method is the same as that of Experimental Example 1. The results are shown in Figure 6 .
[0092] Different metal salt concentration ratios have a great influence on the performance of electrode materials. The presence of uranium pre-activates water molecules and promotes their dissociation. The addition of iron enhances the interaction between metals, thereby significantly improving the electrocatalytic performance. Too much iron will cover up the active sites of the reaction, affect the adsorption of water molecules, and thus inhibit the performance. Figure 6 It can be seen that the preferred uranium-iron molar ratio is 1:10-15.
[0093] Test Example 6
[0094] The electrode materials prepared in Example 1 and Examples 8-12 were subjected to linear sweep voltammetry in a 5wt% KOH solution to explore the effects of different immersion times on material properties. The specific test method is the same as that in Example 1. The results are shown in Figure 7 .
[0095] Different immersion times have little effect on the electrode material, indicating that the replacement reaction is relatively rapid, and the replaced metal can cover the surface of the carrier in a short time and form a strong interaction with the carrier. This fully demonstrates the simplicity and convenience of the method, which is conducive to large-scale production and application.
[0096] Test Example 7
[0097] The electrode materials prepared in Example 1, Example 13, Example 15 and Example 18 were subjected to linear sweep voltammetry test in 5wt% KOH solution to explore the influence of thorium and uranium on the material properties. The specific test method is the same as that of Test Example 1. The results are shown in Figure 8 .
[0098] The electrolytic water splitting and oxygen separation performance of the material has been significantly improved (the effect is relatively inferior to uranium). This shows that it has a pre-activation effect on the adsorbed water molecules. The trace radiation energy carried can penetrate the structure of water molecules, subtly disturbing the electron cloud and hydrogen bond network inside them, thereby activating the dynamic characteristics of water molecules in advance and reducing the overall energy barrier of subsequent chemical reactions.
[0099] Test Example 8
[0100] The electrode material prepared in Example 1 was tested for stability in 5wt% KOH alkaline water and 5wt% KOH seawater to explore the tolerance of the material. The specific test used a saturated Ag / AgCl electrode as the reference electrode and a graphite electrode as the counter electrode to perform a time-current test. At 150 mA·cm -2 The catalytic water splitting was conducted at a current density of about 1000 Å to release oxygen for one week. The results are shown in Fig. 9 .
[0101] After a week of power-on testing, the current density in alkaline water decreased by only 7.9%, and the current density in alkaline seawater decreased by only 11.8%. This shows that the prepared quaternary electrode has a strong structure and excellent stability in both alkaline water and complex seawater, and has great potential in large-scale applications.
Claims
1. A method for preparing a low overpotential anode, characterized in that The following steps are involved: 1) immersing the nickel foam loaded with molybdenum metal after pickling pretreatment into a soaking solution containing uranium and / or thorium metal salt and iron salt to carry out a replacement reaction, and then taking it out and drying it; Wherein, the molar ratio of uranium and / or thorium to iron is 1:10-15; 2) The product obtained in step 1) is calcined in the presence of oxygen at 100-300° C. for 0.5-1.5 h to obtain a low overpotential anode.
2. The preparation method according to claim 1, characterized in that: In step 1), the nickel foam loaded with molybdenum metal is prepared by immersion displacement method, electroplating method or high-temperature reduction method; the mass ratio of nickel to molybdenum is 3-8:
1.
3. The preparation method according to claim 1 or 2, characterized in that: In step 1), the thickness of the nickel foam is 1-2 mm, the pore size is 80-150 ppi, and the area range is 0.0001-10 m 2 .
4. The preparation method according to claim 1 or 2, characterized in that: In step 1), the pickling specifically comprises: placing the nickel foam in 0.5-1.5 mol·L -1 The sample was ultrasonically cleaned in a dilute hydrochloric acid solution for 20-40 minutes, taken out and immersed in anhydrous ethanol for ultrasonic cleaning for 20-40 minutes, and dried.
5. The preparation method according to claim 1, characterized in that: In step 2), The uranium and / or thorium metal salt is uranyl nitrate hexahydrate or thorium nitrate hydrate; The iron salt is one or more of ferric sulfate, ferric nitrate and ferric chloride.
6. The preparation method according to claim 1 or 5, characterized in that: In step 2), The iron content in the soaking solution is 0.05-0.2 mol·L -1 ; The ratio of the area of the nickel foam to the amount of the soaking liquid is 0.8-5cm -2 / mL.
7. The preparation method according to claim 1, characterized in that: In step 2), the replacement reaction time is 10-60 min.
8. Use of the low overpotential anode obtained according to the preparation method according to any one of claims 1 to 7 in electrocatalytic cracking of alkaline water or oxygen evolution from alkaline seawater.
9. The use according to claim 8, characterized in that: The alkaline medium in the alkaline water or alkaline seawater is sodium hydroxide or potassium hydroxide.
10. The use according to claim 9, characterized in that: The concentration of the sodium hydroxide or potassium hydroxide is 1-50 wt %.
Citation Information
Patent Citations
Electrocatalytic oxygen evolution electrode and preparation and application thereof
CN110656348A
Application of uranium-loaded molybdenum disulfide nanosheet in electro-catalysis alkaline hydrogen evolution reaction
CN114507874A
Preparation of uranium-loaded cobaltosic oxide nanosheet and application of uranium-loaded cobaltosic oxide nanosheet in electro-catalysis alkaline oxygen evolution reaction
CN115354359A
Low-overpotential Ni3Fe-based LDH type oxygen evolution electrocatalyst as well as efficient preparation method and application thereof
CN115928123A
Foamed ferronickel-based electrolyzed water bifunctional catalyst and preparation method thereof
CN116949494A
Cited By
Nickel-based electrode material for stable electrolytic hydrogen production under real seawater system and preparation method of nickel-based electrode material
CN120006338A
